MEX-5 enrichment in the C. elegans early embryo mediated by differential diffusion - Daniels, Brian R. (Company of Biologists, 2010)
Specification of germline and somatic cell lineages in C. elegans originates in the polarized single-cell zygote. Several cell-fate determinants are partitioned unequally along the anterior-posterior axis of the zygote, ensuring the daughter cells a unique inheritance upon asymmetric cell division. Recent studies have revealed that partitioning of the germline determinant PIE-1 and the somatic determinant MEX-5 involve protein redistribution accompanied by spatiotemporal changes in protein diffusion rates. Here, we characterize the dynamics of MEX-5 in the zygote and propose a novel reaction/diffusion model to explain both its anterior enrichment and its remarkable intracellular dynamics without requiring asymmetrically distributed binding sites. We propose that asymmetric cortically localized PAR proteins mediate the anterior enrichment of MEX-5 by reversibly changing its diffusion rate at spatially distinct points in the embryo, thus generating a stable concentration gradient along the anterior-posterior axis of the cell. This work extends the scope of reaction/diffusion models to include not only germline morphogens, but also somatic determinants.